A quadratic expression is an expression in which the highest power of unknown is 2. e.g.

• x2 + 9x + 14
• x2 + 14
• x2 – 9

## Factorising quadratic expressions by grouping

The method of factorisation by grouping can be extended even to quadratic expressions. In the previous exercise there were some quadratic expressions we factorised which were however in different form from what we are going to look at right now.

Example

Factorise the following completely

1. x2 + 9x + 14
This expression has 3 terms and we need 4 terms to factorise it by grouping pairs. So we split the middle term into 2 terms as follows.

first we multiply the end terms, x2 and 14 in this case to get 14x2

Then we list the factors of 14x2 and find among them, 2 factors whose sum is 9x, the middle term.

14x2 =

• x × 14x [add these and you get 15x.]
• 2x × 7x [add these and you get 9x.]

Therefore the factors we need are 2x and 7x. Go back to the oroginal expression and replace 9x with these 2 factors.

= x2 + 9x + 14
= x2 + 2x + 7x + 14
then factorise by grouping

= x(x + 2) + 7(x + 2)
= (x + 2)(x + 7)

More Examples

Factorise the following completely

1. a2 + 8a + 15
Multiply 15 and a2 to get 15a2
Find the factors of 15a2 whose sum is 8a
Let me tabulate the process to make it easier to understand.
a ×15a16aNo
3a × 5a8aYes

Replace 8a in the original expression by 3a and 5a
= a2 + 8a + 15
= a2 + 5a + 3a + 15
= a(a + 5) + 3(a + 5)
= (a + 5)(a + 3)

1. b2 – 7b + 10
Lets find factors of 10b2 whose sum is -7b
2b ×5b7bNo
-2b ×-5b-7bYes

= b2 – 7b + 10
= b2 – 2b – 5b + 10
= b(b – 2) – 5(b – 2)
= (b – 2)(b – 5)

However with practice you will soon master the art of finding the factors without tabulating anything.

1. c2 + 4c – 21
Multiply c2 by -21 to get -21c2 and then find the factors of -21c2, whose sum is 4c
Thats 7c and -3c.
= c2 + 7c – 3c – 21
= c(c + 7) – 3(c + 7)
= (c + 7)(c – 3)

1. d2 – 5d – 14
Find the factors of -14d2 whose sum is -5d
Thats -7d and 2d.
= d2 – 7d + 2d – 14
= d(d – 7) + 2(d – 7)
= (d – 7)(d + 2)

As you can see, the process is the same, its only the numbers and factors that keep changing, so the next couple of examples do not have explanations.

1. e2 + 2e – 8
e2 by -8 = -8e2. So find the factors of -8e2 whose sum is 2e
Thats -2e and 4e
= e2 -2e + 4e – 8
= e(e – 2) + 4(e – 2)
= (e + 4)(e – 2)

1. w2 + 5w + 6
w2 by 6 = 6w2. Find the factors of 6w2 whose sum is 5w
Thats 2w and 3w
= w2 + 2w + 3w + 6
= w(w + 2) + 3(w + 2)
= (w + 2)(w + 3)

1. x2 + 5x – 6
x2 by -6 = -6x2. Find the factors of -6x2 whose sum is 5x
Thats -x and 6x
= x2 -x + 6x – 6
= x(x – 1) + 6(x – 1)
= (x – 1)(x + 6)

1. y2 – 5y + 6
y2 by 6 = 6y2. Find the factors of 6y2 whose sum is -5y
Thats -2y and -3y
= y2 – 2y – 3y + 6
= y(y – 2) -3(y – 2)
= (y – 3)(y – 2)

## Difference of 2 squares

A perfect square is a number that has an exact square root, e.g: 1, 4, 9, 16 are perfect squares and their square roots are 1, 2, 3, 4 respectively. We can also have perfect squares among algebraic terms, e.g x2 is a perfect square whose square root is x.

Now when we talk about difference of 2 squares we mean a quadratic equation like this (x2 – 4) in which we have 2 squares subtracting each other.

Take note that:

• (x2 + 4) is not difference of 2 squares because those squares are not subtracting each other.
• (x2 – 4x) is not difference of 2 squares because 4x is not a perfect square due to the presence of x.
• (x2 – 4y2) is difference of 2 squares.

Example

Factorise the following:

1. x2 – 4
Find the square roots of both squares and express them in 2 brackets, first as a sum and then as a difference
= (x + 2)(x – 2)

1. r2 – 25
= (r + 5)(r – 5)

1. x2 – y2
= (x + y)(x – y)

1. x2 – 36y2
= (x – 6y)(x + 6y)

1. a2b2 – 9c2
= (ab + 3c)(ab – 3c)

#### Disguised difference of 2 squares

Sometimes the squares can be disguised until you first pull out a common factor.

Examples

1. 2b2 – 18
As it is its not difference of 2 squares, until we pull out the common factor 2.
= 2(b2 – 9)
= 2(b + 3)(b – 3)

1. ax2 – ab2
= a(x2 – b2)
= a(x + b)(x – b)

Examples

1. x2 – 4x
= x(x – 4)

1. m2 + 10m
= m(m + 10)